Culture and Organizational Learning - Cook, S.D. Noam; Yanow, Dvora (Journal of management inquiry, 2011)
Traditionally, theories of organizational learning have taken one of two approaches that share a common characterization of learning but differ in focus. One approach focuses on learning by individuals in organizational contexts; the other, on individual learning as a model for organizational action. Both base their understanding of organizational learning on the cognitive activity of individual learning. However, there is something organizations do that may be called organizational learning, that is neither individuals learning in organizations nor organizations employing processes akin to learning by individuals. This form of organizational learning can be seen in the case of three small workshops that make "the finest flutes in the world." This essay proposes a perspective on organizational learning, drawing on the concept of organizational culture, that can be useful in understanding the case. This perspective provides a fruitful basis for exploring the above distinctions in both theory and practice.